2021
DOI: 10.1371/journal.pone.0250867
|View full text |Cite
|
Sign up to set email alerts
|

The European tomato market. An approach by export competitiveness maps

Abstract: Most empirical studies examining the export competitiveness of a country in a target market are undertaken by focusing on supply, only analysing the group of competing countries. In addition, if the target market to be analysed is extensive, like the European Union, it is generally analysed as a whole. This study presents an evaluation of the tomato export competitiveness, from a differentiated demand perspective, analysing its main customers markets in the context of European Union. The methodological framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…They concluded that changes in export competitiveness in the region are primarily driven by expansions of market share within the EU. Capobianco-Uriarte [58] also employed the CMS approach to examine the European tomato market.…”
Section: Measurement Of Competitivenessmentioning
confidence: 99%
“…They concluded that changes in export competitiveness in the region are primarily driven by expansions of market share within the EU. Capobianco-Uriarte [58] also employed the CMS approach to examine the European tomato market.…”
Section: Measurement Of Competitivenessmentioning
confidence: 99%
“…European tomato production, according to FAOSTAT (Statistics Division of the Food and Agriculture Organization of the United Nations) data [7], steadily represents around 13% of global tomato production. In 2020, almost 17 million tons of tomatoes were harvested in the European Union [8,9]. The most important EU producer was Italy, contributing 38% to the total EU production.…”
Section: Introductionmentioning
confidence: 99%
“…Among Italy's processed tomato production, mashed tomatoes represent about 50% of packaged tomato volume [12]. The processed tomato sector is also important for Italy's international trade [9] since 60% of Italian production is exported to foreign markets [6]. With 747,000 tons of exported pasta tomatoes and 1.432 million tons of canned tomatoes, Italy is the leading exporter of tomato products [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies of this type are difficult to find, most of the research, in Europe, is focus on competitiveness of agricultural products [ 5 , 6 ], volatility of prices [ 7 ], sustainability of food system [ 8 ], the assessment of biological risk–diseases in animals [ 9 , 10 ], environmental risk [ 11 ], negative impacts of the agricultural commodities on ecosystems [ 12 ], and few analysis on commodities diversification and their impacts.…”
Section: Literature Review and Contextmentioning
confidence: 99%